A Study on Colouring and chromatic number of graphs (International Journal of Food and Nutritional Sciences, 2022)
In this paper, we discuss the significance of various graph colouring approaches using pictures. We determine the graph colouring characteristics such as chromatic, achromatic, and pseudoachromatic number for a variety of graphs in this study. We compute chromatic and achromatic numbers for a novel class of graphs, such as the central graph of a cycle graph ????(????????) and the central graph of a jellyfish ????, in this study (????, ????). The applications of various graph colouring approaches in domains such as automated differentiation, mobile networks, optical networks, medical data mining, game theory, and radio networks are discussed in this research article..